Neutralizing and protective epitopes of the 2009 pandemic influenza H1N1 hemagglutinin. Issue 3 (5th November 2012) - Schmeisser, Falko; Friedman, Rachel; Besho, Joseph; Lugovtsev, Vladimir; Soto, Jackeline; Wang, Wei; Weiss, Carol; Williams, Ollie; Xie, Hang; Ye, Zhiping; Weir, Jerry P.
<x xml:space="preserve">Abstract</x> Aims and Methods To facilitate antigenic characterization of the influenza A 2009 pandemic H1N1 [A(H1N1)pdm09] hemagglutinin (HA), we generated a panel of murine monoclonal antibodies (mAbs) using as the immunogen mammalian‐derived virus‐like particles containing the HA of the A/California/04/2009 virus. The antibodies were specific for the A/California/04/2009 HA, and individual mAbs suitable for use in several practical applications including ELISA, immunofluorescence, and Western blot analysis were identified. Results and Conclusions As the panel of mAbs included antibodies with hemagglutination inhibition (HI) and virus neutralizing activities, this allowed identification and characterization of potentially important antigenic and neutralizing epitopes of the A/California/04/2009 HA and comparison of those epitopes with the HAs of other influenza viruses including seasonal H1N1 viruses as well as the A/South Carolina/1918 and A/New Jersey/1976 H1N1 viruses. Three mAbs with the highest HI and neutralizing titers were able to provide passive protection against virus challenge. Two other mAbs without HI or neutralizing activities were able to provide partial protection against challenge. HA epitopes recognized by the strongest neutralizing mAbs in the panel were identified by isolation and selection of virus escape mutants in the presence of individual mAbs. Cloned viruses resistant to HI and antibody neutralization were sequenced to identify mutations, and two unique mutations (D127E and G155E) were identified, both near the antigenic site Sa. Using human post‐vaccination sera, however, there were no differences in HI titer between A/California/04/2009 and either escape mutant, suggesting that these single mutations were not sufficient to abrogate a protective antibody response to the vaccine.